A Study on Steering Characteristics of Pilot Mining Robot(MineRo II) on Extremely Cohesive Soft Soil - Hyung-woo Kim (International Marine Minerals Society, 2011)
This paper concerns about steering characteristics of pilot mining robot, named MineRo II, crawling on extremely cohesive soft soil using dynamic simulation software. The MineRo-II for deep-seabed manganese nodules, which aims at the use for pilot mining test, was manufactured in 1/5 scale of commercial mining capacity (see Fig. 1).